Human INO80/YY1 chromatin remodeling complex transcriptionally regulates the BRCA2- and CDKN1A-interacting protein (BCCIP) in cells. Issue 10 (17th August 2016) - Su, Jiaming; Sui, Yi; Ding, Jian; Li, Fuqiang; Shen, Shuang; Yang, Yang; Lu, Zeming; Wang, Fei; Cao, Lingling; Liu, Xiaoxia; Jin, Jingji; Cai, Yong
Abstract: The BCCIP (BRCA2- and CDKN1A-interacting protein) is an important cofactor for BRCA2 in tumor suppression. Although the low expression of BCCIP is observed in multiple clinically diagnosed primary tumor tissues such as ovarian cancer, renal cell carcinoma and colorectal carcinoma, the mechanism of how BCCIP is regulated in cells is still unclear. The human INO80/YY1 chromatin remodeling complex composed of 15 subunits catalyzes ATP-dependent sliding of nucleosomes along DNA. Here, we first report that BCCIP is a novel target gene of the INO80/YY1 complex by presenting a series of experimental evidence. Gene expression studies combined with siRNA knockdown data locked candidate genes including BCCIP of the INO80/YY1 complex. Silencing or over-expressing the subunits of the INO80/YY1 complex regulates the expression level of BCCIP both in mRNA and proteins in cells. Also, the functions of INO80/YY1 complex in regulating the transactivation of BCCIP were confirmed by luciferase reporter assays. Chromatin immunoprecipitation (ChIP) experiments clarify the enrichment of INO80 and YY1 at +0.17 kb downstream of the BCCIP transcriptional start site. However, this enrichment is significantly inhibited by either knocking down INO80 or YY1, suggesting the existence of both INO80 and YY1 is required for recruiting the INO80/YY1 complex to BCCIP promoter region. Our findings strongly indicate that BCCIP is a potential target gene of the INO80/YY1 complex.